Acute Effects of Resistance Training with Blood Flow Restriction on Achilles Tendon Thickness - Picón-Martínez, Moisés (J Hum Kinet, 2021)
The Achilles tendon is one of the strongest and thickest tendons of the human body. Several studies have reported an immediate decrease in Achilles tendon thickness after a single bout of resistance training. However, the effects of blood flow restriction training on Achilles tendon thickness have not been investigated. The purpose of this study was to investigate the acute effects of different regimens of resistance training on Achilles tendon thickness. Fiftytwo participants (27.3 ± 7 years; 177.6 ± 11 cm; 72.2 ± 13.7 kg) were randomly allocated into one of the three groups: low-intensity exercise without (LI, n = 13) and with blood flow restriction (LI-BFR, n = 24), and high-intensity exercise (HI, n = 15). Participants from LI and LI-BFR groups performed four sets (1 x 30 + 3 x 15 reps) at 30% 1RM, while the HI group performed four sets (1 x 30 with 30% 1RM + 3 x 10 reps with 75% 1RM). All groups performed a plantar flexion exercise. For the LI-BFR group, a blood pressure cuff was placed on the dominant calf and inflated at 30% of the individual´s occlusion pressure (47.6 ± 19.8 mmHg). Sonographic images of Achilles tendon thickness were taken at pre, immediately after, 60 min and 24 h following acute bouts of exercise. Achilles tendon thickness was significantly reduced immediately after, 60 min and 24 h post-LI-BFR exercise (pre: 4.4 ± 0.4 mm vs. IA: 3.8 ± 0.4 mm vs. 60 min: 3.7 ± 0.3 mm vs. 24 h: 4.1 ± 0.3 mm; p < 0.001), whereas Achilles tendon thickness was unchanged for HI and LI groups (p > 0.05). These results suggest that blood flow restriction training may be an effective strategy to stimulate a positive response in Achilles tendon thickness.